Tractor energy requirements in disc harrow systems. - Serrano, João M. (2009)
Soil working operations in conventional farming systems involving the use of the tractor are some of the operations which incur the highest energy costs. The sustainability of such systems requires a strictly-controlled management of resources leading to a significant reduction in crop-production costs derived from savings in fuel consumption. The configuration of the tractor-harrow combination, based on the measurement of the draught required under operational conditions provides the manufacturers with a reliable indication of the recommended power required for each model of harrow produced. With this type of information farmers can take decisions regarding the selection of a suitable tractor-implement combination for their farms. As a consequence there is improved tractor-harrow productivity and field efficiency. This study centred on the validation of the mathematical models used to estimate the draught of disc harrows in medium textured soils presented by ASABE. A three-year research project was developed to study tractor-implement dynamics in tillage operations. The field tests were performed under real working conditions, using more than twenty four-wheel-drive tractors and trailed disc harrows combinations, in different soil types. The tractors were instrumented and the measured parameters were: forward speed, slip, engine speed, draught and fuel consumption per hour. The tractors were also submitted to dynamometer tests for measuring PTO power and speed and the engine fuel consumption per hour. The results allow led to the development of a quadratic equation that corresponds to an adaptation of the linear model of ASABE to estimate the draught of the disc harrows in undisturbed loamy soils, not only as a function of implement mass and soil type, but also as a function of speed, working depth and soil conditions. Under these conditions, a ratio of tractor power to implement width of 25 to 33 kW m-1 is suggested. The data also show the existence of a linear relationship between the fuel consumption per hectare and the specific draught, for the range of 4 to 9 kN m-1, valid for dry, undisturbed loamy soils.